2013
DOI: 10.1021/es401006k
|View full text |Cite
|
Sign up to set email alerts
|

Anthropogenic Mercury Flows in India and Impacts of Emission Controls

Abstract: India is a major emitter of mercury, a pollutant of global importance. However, quantitative information on mercury flows in the country is lacking. Here, we quantify major transfer pathways for anthropogenic mercury, its emissions to the environment (air, water, soil), and storage in consumer products and anthropogenic sinks (e.g., landfills) in India in the period 2001-2020, and evaluate the potential influence of six pollution control measures. Total mercury emissions in India were approximately 415 tonnes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
78
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(79 citation statements)
references
References 33 publications
0
78
0
1
Order By: Relevance
“…Studies have suggested comparable Hg inputs through atmospheric wet deposition from distant sources. 18,39,45,46 Long-distance transport of Hg through atmospheric circulation is one of the most important pathways for Hg accumulation in the soils of the TP. 39 Thus, we consider factor 4 to be an anthropogenic emission source dominated by wet deposition, which may be partially supported by a positive relationship between average annual precipitation and the soil Hg content of the TP (Table 3).…”
Section: 22mentioning
confidence: 99%
“…Studies have suggested comparable Hg inputs through atmospheric wet deposition from distant sources. 18,39,45,46 Long-distance transport of Hg through atmospheric circulation is one of the most important pathways for Hg accumulation in the soils of the TP. 39 Thus, we consider factor 4 to be an anthropogenic emission source dominated by wet deposition, which may be partially supported by a positive relationship between average annual precipitation and the soil Hg content of the TP (Table 3).…”
Section: 22mentioning
confidence: 99%
“…Previous studies have demonstrated that anthropogenic emissions of atmospheric contaminants were particularly large in the Indian subcontinent (Streets et al, 2003a(Streets et al, , 2003b(Streets et al, , 2009Ohara et al, 2007;Burger Chakraborty et al, 2013), contributing a significant fraction of anthropogenic emissions in the world. In our present study, trajectory analysis has indicated that elevated atmospheric water vapor Hg concentrations were generally observed when air masses passed through the Indian subcontinent for a period of time before arriving at our study site (Fig.…”
Section: Case Studies For the Potential Sources Of Hg In Atmospheric mentioning
confidence: 99%
“…Among the various regions, Asia has become the world's largest contributor of anthropogenic atmospheric contaminants, responsible for over half of the global emission (Streets et al, 2003a(Streets et al, , 2003bOhara et al, 2007). Most importantly, the anthropogenic emissions of contaminants (e.g., Hg) from the Indian subcontinent will most likely continue to increase during a long time of future (Ohara et al, 2007;Streets et al, 2009;Pacyna et al, 2010;Burger Chakraborty et al, 2013), implying that the potential impacts of transboundary air pollution on increasing loadings of exotic contaminants to the fragile ecosystems of the Tibetan Plateau should no longer be ignored. As a consequence, further studies addressing the environmental impact of transboundary air pollution to the ecosystems of the Tibetan Plateau are urgently needed and the effectiveness of stringent Hg emission controls in the Indian subcontinent is called upon by the recently signed Minamata Convention for Hg.…”
Section: Below-cloud Scavenging Of Hg and Environmental Implications mentioning
confidence: 99%
“…The rapid growth of industrialization in the last century has increased the emission of toxic metal species such as elemental mercury in the atmosphere [1][2][3][4][5][6][7]. It is of high importance to control the emission of these metal species from common industrial sources in order to reduce the advert effect they are having on the environment as well as human health.…”
Section: Introductionmentioning
confidence: 99%